2016
DOI: 10.1007/s00203-016-1272-y
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of Oxalobacter formigenes: an in vitro examination

Abstract: Oxalobacter formigenes (O. formigenes) is a nonpathogenic, Gram-negative, obligate anaerobic bacterium that commonly inhabits the human gut and degrades oxalate as its major energy and carbon source. Results from a case-controlled study suggested that lack of O. formigenes colonization is a risk factor for recurrent calcium oxalate stone formation. Hence, O. formigenes colonization may prove to be an efficacious method for limiting calcium oxalate stone risk. However, challenges exist in the preparation of O. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…It is known that several anaerobic bacteria show oxygen tolerance and possess systems to respond to oxygen (46)(47)(48). In this study, we demonstrated that O. formigenes survives in fecal pellets excreted from animals monocolonized with O. formigenes, which is consistent with our recent finding that O. formigenes survives in static broth cultures exposed to the air (49). Of note, the genomes of two O. formigenes strains (50) and the proteome of O. formigenes OxCC13 (51) contain superoxide dismutase, which may play a key role in the survival of O. formigenes during periods of oxygen exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is known that several anaerobic bacteria show oxygen tolerance and possess systems to respond to oxygen (46)(47)(48). In this study, we demonstrated that O. formigenes survives in fecal pellets excreted from animals monocolonized with O. formigenes, which is consistent with our recent finding that O. formigenes survives in static broth cultures exposed to the air (49). Of note, the genomes of two O. formigenes strains (50) and the proteome of O. formigenes OxCC13 (51) contain superoxide dismutase, which may play a key role in the survival of O. formigenes during periods of oxygen exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, group-housed GF/OxF animals had small numbers of viable O. formigenes organisms throughout the gastrointestinal tract. This finding not only highlights the coprophagic behavior of group-housed mice in regular cages but also supports previous in vitro reports showing that O. formigenes tolerates exposure to acid and bile (3,49).…”
Section: Discussionsupporting
confidence: 90%
“…Among them, oxalate occupies the vast majority, exceeding 85%. The microbiota refers to the entire microbial population that colonizes in a specific location and includes not only bacteria but also other microorganisms such as fungi, archaea, viruses, and protozoa [ 8 ]. The scientific community has shown great interest in the gut microbiota in recent years; the gut microbiota is associated with many human diseases, such as intestinal diseases such as inflammatory bowel disease (IBD) [ 9 ] and irritable bowel syndrome (IBS) [ 10 ], metabolic diseases such as obesity and diabetes [ 11 ], and allergic diseases [ 12 ] to neurodevelopmental diseases, although the strength of some evidence is not sound in many of them.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Adlercreutzia only has one species, namely, A. equolifaciens , which can produce equol [ 60 ]. The genus Oxalobacter commonly inhabits the intestine and can degrade oxalate as its major energy [ 61 ] (Liu et al, 2016). The desulfitobacter spp.…”
Section: Discussionmentioning
confidence: 99%